The Effect of Guided Inquiry-Based Practicum Learning and Prior Knowledge on Learning Outcomes and Science Process Skills of High School Students on Solubility and Solubility Products - Jakub Saddam Akbar; I Wayan Dasna; Surjani Wonorahardjo (Jurnal Pendidikan Sains, 2019)
Abstract: This study aimed to compare the students’ learning outcome and science process skill that learned by two different methods viewed from prior knowledge. This study used the quasi-experimental design. The research‘s instruments were student‘s learning outcome and science process skill test. Data were analyzed using by MANOVA. The results showed that: (1) there was differences in student‘s learning outcome and science process skill that learned with guided inquiry based laboratory activities and verification based laboratory; (2)  there was no interaction between learning methods in laboratory activity and prior knowledge on student‘s learning outcome. Thus, the guided inquiry strategy has enhanced student’s learning outcome and science process skill.Key Words: guided inquiry, laboratory activity, prior knowledgeAbstrak: Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar dan keterampilan proses sains siswa yang dibelajarkan dengan dua metode berbeda ditinjau dari pengetahuan awal. Penelitian ini menggunakan rancangan penelitian eksperimen semu. Instrumen pengukuran yang digunakan dalam penelitian ini adalah tes keterampilan proses sains dan hasil belajar siswa. Data dianalisis menggunakan MANOVA. Hasil penelitian menunjukkan bahwa: (1) ada perbedaan hasil belajar dan keterampilan proses sains siswa yang dibelajarkan dengan praktikum inkuiri terbimbing dan praktikum verifikasi, (2) tidak terdapat interaksi antara strategi pembelajaran dalam kegiatan praktikum dan pengetahuan awal terhadap hasil belajar siswa. Simpulannya adalah praktikum inkuiri terbimbing dapat meningkatkan hasil belajar dan keterampilan proses sains siswa.Kata kunci: inkuiri terbimbing, kegiatan praktikum, pengetahuan awal